Keratins K2 and K10 are essential for the epidermal integrity of plantar skin. Issue 1 (January 2016) - Fischer, Heinz; Langbein, Lutz; Reichelt, Julia; Buchberger, Maria; Tschachler, Erwin; Eckhart, Leopold
Highlights: We generated mice deficient for both keratins K2 and K10. K2/K10 double knockout mice developed calluses on the soles. Loss of K2 and K10 was partially compensated by upregulation of K1, K9 and K16. K16 co-localized with K1 but not with K6, indicating K1/K16 heterodimerization. Abstract: Background: K1 and K2 are the main type II keratins in the suprabasal epidermis where each of them heterodimerizes with the type I keratin K10 to form intermediate filaments. In regions of the ears, tail, and soles of the mouse, only K2 is co-expressed with K10, suggesting that these keratins suffice to form a mechanically resilient cytoskeleton. Objective: To determine the effects of the suppression of both main keratins, K2 and K10, in the suprabasal plantar epidermis of the mouse. Methods: Krt2 −/− Krt10 −/− mice were generated by crossing Krt2 −/− and Krt10 −/− mice. Epidermal morphology of soles of hind-paws was examined macroscopically and histologically. Immunofluorescence analysis and quantitative PCR analysis were performed to analyze the expression of keratins in sole skin of wildtype and Krt2 −/− Krt10 −/− mice. Highly abundant proteins of the sole stratum corneum were determined by electrophoretic and chromatographic separation and subsequent mass spectrometry. Results: K2 and K10 are the most prominent suprabasal keratins in normal mouse soles with the exception of the footpads where K1, K9 and K10 predominate. Mice lacking both K2 and K10 were viable and developed epidermal acanthosis and hyperkeratosis in inter-footpad epidermis of the soles. The expression of keratins K1, K9 and K16 was massively increased at the RNA and protein levels in the soles of Krt2 −/− Krt10 −/− mice. Conclusions: This study demonstrates that the loss of the main cytoskeletal components of plantar epidermis, i.e. K2 and K10, can be only partly compensated by the upregulation of other keratins. The thickening of the epidermis in the soles of Krt2 −/− Krt10 −/− mice may serve as a model for pathomechanistic aspects of palmoplantar keratoderma.